Measurement and interpretation of moments in inclusive semileptonic decays (B)over-bar -> Xcl(nu)over-bar - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2010)
We present results for the moments of observed spectra in inclusive semileptonic B-meson decays to charm hadrons B̄→Xc -ν̄. Moments of the hadronic-mass and the combined mass-and-energy spectra for different minimum electron or muon momenta between 0.8 and 1.9GeV/c are obtained from a sample of 232×106 Υ(4S)→BB̄ events, collected with the BABAR detector at the PEP-II asymmetric-energy B-meson factory at SLAC. We also present a reevaluation of the moments of electron-energy spectra and partial decay fractions B(B̄→Xce-ν̄) for minimum electron momenta between 0.6 and 1.5GeV/c based on a sample of 51×106 Υ(4S)→BB̄ events. The measurements are used for the extraction of the total decay fraction, the Cabibbo-Kobayashi-Maskawa (CKM) matrix element |Vcb|, the quark masses mb and mc, and four heavy-quark QCD parameters in the framework of a Heavy-Quark Expansion (HQE). We find B(B̄→Xc -ν̄)= (10.64±0.17±0.06)% and |Vcb|=(42.05±0.45±0.70) ×10-3. © 2010 The American Physical Society.